The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.bbr.2007.03.037
|View full text |Cite
|
Sign up to set email alerts
|

The β2 adrenergic receptor regulates morphine tolerance and physical dependence

Abstract: Adaptations to the chronic administration of opioids reduce the utility of these drugs in treating pain and support addiction. Recent genetics-based approaches have implicated the β2 adrenergic receptor (β2-AR) in controlling some of these responses. We do not know, however, whether this receptor can modulate tolerance, dependence or changes in gene expression caused by chronic opioid administration. For our studies we used C57BL/6 mice and β2-AR knockout mice in the FVB background. Morphine dose response rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 46 publications
(70 reference statements)
3
42
1
Order By: Relevance
“…Studies have shown an increased synthesis of SP in cultured DRG neurons, and our own data show an up-regulation of pre-protachykinin mRNA in DRG tissue from morphine treated mice 6, 44, 45 . The spinal cord content of SP, present mostly in the terminals of afferent nerve fibers is increased in morphine treated mice 45 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Studies have shown an increased synthesis of SP in cultured DRG neurons, and our own data show an up-regulation of pre-protachykinin mRNA in DRG tissue from morphine treated mice 6, 44, 45 . The spinal cord content of SP, present mostly in the terminals of afferent nerve fibers is increased in morphine treated mice 45 .…”
Section: Discussionsupporting
confidence: 63%
“…Incision and nociceptive testing procedures began approximately 18 hours after the final dose of morphine or saline. This morphine administration protocol has been used extensively by the lab in studying opioid tolerance, dependence and hyperalgesia 42, 43, 45 . The selective NK-1 receptor antagonist LY303870 was obtained from Lilly Pharmaceuticals and prepared in sterile 0.9% saline and administered (30 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Following the results of a genetic study linking the b-adrenergic receptor to OIH [210], speculation arose regarding the clinical therapeutic effect of propranolol in treating OIH. Accordingly, Chu et al [47] conducted a clinical trial in which propranolol effectively eliminated secondary hyperalgesia in healthy volunteers receiving remifentanil infusion and undergoing experimental pain testing ( Table 3).…”
Section: Propranololmentioning
confidence: 99%
“…Exposure to high doses of opioids during surgery may result in postoperative OIH and the spinal adrenergic beta-2 receptors may contribute to the neuroadaptive processes related to OIH [22]. In a recent study where electrical stimulation was used to generate areas of secondary mechanical hyperalgesia, remifentanil infusion increased the areas to 141 % of the baseline.…”
Section: Discussionmentioning
confidence: 98%